Liquid fuel ignition features during its spilling on the metallic substrate heated up to high temperatures; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Vysokomornaya O. V. Olga Valeryevna (2015, 2015)
Title screen